When Is It Appropriate to Take Off the Mask? Signaling Pathways That Regulate ß(1,3)-Glucan Exposure in Candida albicans - Chen, Tian; Wagner, Andrew S.; Reynolds, Todd B. (Frontiers in Fungal Biology, 2022)
Candida spp. are an important source of systemic and mucosal infections in immune compromised populations. However, drug resistance or toxicity has put limits on the efficacy of current antifungals. The C. albicans cell wall is considered a good therapeutic target due to its roles in viability and fungal pathogenicity. One potential method for improving antifungal strategies could be to enhance the detection of fungal cell wall antigens by host immune cells. (1,3)-glucan, which is an important component of fungal cell walls, is a highly immunogenic epitope. Consequently, multiple host pattern recognition receptors, such as dectin-1, complement receptor 3 (CR3), and the ephrin type A receptor A (EphA2) are capable of recognizing exposed (unmasked) (1,3)-glucan moieties on the cell surface to initiate an anti-fungal immune response. However, (1,3)-glucan is normally covered (masked) by a layer of glycosylated proteins on the outer surface of the cell wall, hiding it from immune detection. In order to better understand possible mechanisms of unmasking (1,3)-glucan, we must develop a deeper comprehension of the pathways driving this phenotype. In this review, we describe the medical importance of (1,3)-glucan exposure in anti-fungal immunity, and highlight environmental stimuli and stressors encountered within the host that are capable of inducing changes in the levels of surface exposed (1,3)-glucan. Furthermore, particular focus is placed on how signal transduction cascades regulate changes in (1,3)-glucan exposure, as understanding the role that these pathways have in mediating this phenotype will be critical for future therapeutic development.